Volatile fingerprints of Torreya grandis hydrosols under different downstream processes using HS-GC–IMS and the enhanced stability and bioactivity of hydrosols by high pressure homogenization. (September 2022) - Yao, Lingyun; Sun, Junyan; Liang, Yi; Feng, Tao; Wang, Huatian; Sun, Min; Yu, Wanguo
Abstract: Torreya grandis seed arils contain high level of essential oils with various bioactive properties, while the co-produced hydrosols have seldom been investigated and traditionally discarded. In this work, hydrodistillation separated hydrosols of T. grandis were treated with different downstream methods including membrane filtration and homogenization. The volatile composition, stability, and antioxidant activity of T. grandis hydrosols were investigated by HS-GC-IMS, LUMi-Sizer, and in vitro/in vivo methods respectively for the first time. HS-GC-IMS analysis demonstrated that filtered hydrosol (FH) revealed great changes in volatile compounds as compared to untreated hydrosol (UH) and homogenized hydrosols. The stability results suggested that filtration and high-pressure homogenization treatment greatly enhanced the stability of the hydrosol. In vitro bioactivity analysis revealed that FH was less effective in enhancing antioxidant property of hydrosols as compared to high-pressure homogenization (HH) treatment. In addition, HH showed significant enhancement of antioxidant effects in Caenorhabditis elegans assay. These results demonstrated that high-pressure homogenization was an effective way to enhance the stability and bioactivity of T. grandis hydrosols, which could be served as a novel downstream method for producing high quality hydrosols obtained from T. grandis as well as other plant materials. Highlights: Volatile fingerprints of T. grandis hydrosols were established using HS-GC-IMS. HS-GC-IMS coupled with PCA could be used for quality control of hydrosols. Filtration and high-pressure homogenization improved the stability of hydrosols. High-pressure homogenization enhanced the antioxidant activity of hydrosols.